A Multidisciplinary Concept of Islamic Religious Education Material Based on the Integration of Reason and Revelation - Zaini Fasya; M. Sulaiman M. Sulaiman; Siti Khoirun Nisak (EDUJAVARE: International Journal of Educational Research, 2026)
Islamic Religious Education (PAI) faces the challenge of fostering learning that goes beyond mere mastery of religious knowledge to cultivate critical, contextual, and adaptive thinking skills capable of keeping pace with advancements in science and technology. This article aims to analyze and formulate a multidisciplinary concept for PAI content grounded in the integration of reason and revelation as an epistemological foundation to guide the development of learning materials. The study employs a qualitative approach, specifically library research. Data were gathered from the Qur'an, Hadith, scholarly books, accredited national and reputable international journal articles, and various literature concerning Islamic education, the integration of knowledge, and multidisciplinary approaches. Data analysis was conducted using content analysis, involving stages of data reduction, categorization, interpretation, and conceptual synthesis. The findings indicate that the integration of reason and revelation serves as an epistemological foundation capable of eliminating the dichotomy between religious and secular sciences in the development of PAI content. A multidisciplinary approach enables PAI material to be developed holistically by integrating various disciplines such as tafsir (exegesis), Hadith, fiqh (jurisprudence), philosophy, psychology, sociology, history, science, technology, and environmental science. Reconstructing the material in this way results in learning that is more contextual and meaningful, while also fostering 21st-century competencies including critical thinking, creativity, collaboration, communication, and digital literacy alongside the formation of Islamic character.